2010
DOI: 10.1111/j.1439-0396.2010.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin and mRNA expression of lipogenesis and lipolysis‐related factors in bovine adipose tissue around parturition

Abstract: The objective was to study changes in plasma leptin concentration parallel to changes in the gene expression of lipogenic- and lipolytic-related genes in adipose tissue of dairy cows around parturition. Subcutaneous fat biopsies were taken from 27 dairy cows in week 8 antepartum (a.p.), on day 1 postpartum (p.p.) and in week 5 p.p. Blood samples were assayed for concentrations of leptin and non-esterified fatty acids (NEFA). Subcutaneous adipose tissue was analysed for mRNA abundance by real-time qRT-PCR encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
(59 reference statements)
5
16
0
Order By: Relevance
“…In addition, leptin concentrations decreased in both groups at parturition, which was likely caused by the characteristic negative energy balance that occurs at the onset of lactation (Vernon et al, 2002;Gross et al, 2011). Those results are in agreement with Sadri et al (2011) who observed decreased leptin concentrations 1 d postpartum compared with values obtained 8 wk prepartum. Singh et al (2014) described that adiponectin concentrations also decreased as a consequence of the onset of lactation; however, in our study adiponectin remained unchanged throughout the entire study period.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, leptin concentrations decreased in both groups at parturition, which was likely caused by the characteristic negative energy balance that occurs at the onset of lactation (Vernon et al, 2002;Gross et al, 2011). Those results are in agreement with Sadri et al (2011) who observed decreased leptin concentrations 1 d postpartum compared with values obtained 8 wk prepartum. Singh et al (2014) described that adiponectin concentrations also decreased as a consequence of the onset of lactation; however, in our study adiponectin remained unchanged throughout the entire study period.…”
Section: Discussionsupporting
confidence: 94%
“…Insulin has been described to stimulate secretion of leptin (Block et al, 2001;Sadri et al, 2011) and adiponectin (Blumer et al, 2008) by the adipocytes. In the present study, the 5-HTP dosage did not affect either leptin or adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In order to address these questions, we conducted in vitro signaling studies and checked whether metreleptin-regulated differentiation and lipolysis is modulated by STAT3 signaling in hPA. It has been shown that overexpression of the leptin gene in adipocytes and increased circulating levels of leptin may contribute to enhance lipolysis in obesity (Sadri et al 2011). Similarly, we observed that in vitro administration of metreleptin induces lipolysis in both SC-and OM-derived hPA.…”
Section: Discussionsupporting
confidence: 78%
“…The role of leptin is well documented in rodents and humans, increasing lipolysis and decreasing lipogenesis in the adipose tissues or in the liver (Havel et al, 2004;Sadri et al, 2011), but it is more poorly understood in ruminants (Chilliard et al, 2005). Chilliard et al (2005) suggested that fatty acids, particularly linoleic, could stimulate leptin expression in ruminants as well as in rodents.…”
Section: Introductionmentioning
confidence: 99%